Interstitial fauna of the Sava River in Eastern Slovenia - Simona Prevorčnik; Anja Remškar; Cene Fišer; Boris Sket; Gregor Bračko; Teo Delić; Nataša Mori; Anton Brancelj; Maja Zagmajster (Natura Sloveniae)
Interstitial water that occupies the pore spaces within unconsolidated sediments is a unique habitat, inhabited by surface as well as exclusively subterranean species (stygobionts). The best studied of all interstitial habitats is the hyporheic zone, an interface between surface water and groundwater (phreatic zone) environments. The Sava River in central Slovenia (i.e., at the Ljubljana alluvial plain) readily qualifies as one of the global hotspots of interstitial biodiversity, while data from other river sections are lacking. In 2015, we sampled two gravel bars on the final Slovenian section of the river (Eastern Slovenia), and collected nine samples per site using the Bou-Rouch pumping method. At »Čatež ob Savi« and »Obrežje« sites, at least 26 invertebrate species with 14 stygobionts and 25 invertebrate species with 13 stygobionts were identified, respectively. Altogether, 33 invertebrate taxa with 16 stygobionts were recorded, which increased the previously known interstitial stygobiotic richness of the Sava River in Slovenia by eight species (to 37 species). Three species of the stygobiotic amphipod genus Niphargus were recorded in Slovenia for the first time, one of which is even a new species to science. We discuss the novel results in the context of current national conservation practices.